Why do Patients with Severe Mental Illness Smoke Cigarettes? - Paige Nicole Prologo-Richardson; David Michael Paternite; Emma Wolinsky; Mark Houdi; Jacob Schmieder; Catherine Howell; Alyssa Davis; Britta Eldridge; Charlotte Lennox; Carly Kelley; Jamie Dowling; Chandani Lewis (Translation: The University of Toledo Journal of Medical Sciences, 2024)
The disparity in rates of cigarette smoking between patients with severe mental illnesses (SMIs) and the general population is a well-documented phenomenon. With over 30% of tobacco sales annually being accounted for by patients with SMIs, smoking is a significant modifiable risk factor within this population. Previous research has hypothesized that this increased rate of smoking may be linked to genetic predisposition, self-medication, and as a means of coping with the negative stigma towards those with SMI. This study focuses on the motivating factors that drive these patients to start smoking as well as the emotional changes that take place once smoking becomes routine. Qualifying patients included those who currently smoked cigarettes and had a previous diagnosis of an SMI. Two surveys were administered to patients, one of which gathered objective reasons for smoking (i.e. imitation, distraction, pleasure) while the other gathered subjective changes in their emotional states as they continued to smoke (i.e. changes in happiness, calmness, sociability, etc). Our study found that the two primary reasons these patients began smoking were imitation and feelings of calmness while the two primary reasons for continuing to smoke were addiction and habit. Our study also found that patients felt significantly less happy and less sociable now compared to when they first started smoking cigarettes. This data challenges the belief that using cigarettes provides positive emotional reinforcement and can be used by healthcare professionals to create effective cessation strategies that will likely be different than those used for the general population.